A Universal Method of Producing Transparent Electrodes Using Wide‐Bandgap Materials. (11th November 2013) - Kim, Hee‐Dong; An, Ho‐Myoung; Kim, Kyoung Heon; Kim, Su Jin; Kim, Chi Sun; Cho, Jaehee; Schubert, E. Fred; Kim, Tae Geun
<x xml:space="preserve">Abstract</x> A UV light‐emitting diode (LED) is an eco‐friendly optical source with diverse applications. However, currently, the external quantum efficiency (EQE) of AlGaN‐based UV LEDs, particularly in the UV‐C band (<280 nm), is very low (<11%) mainly due to a large optical absorption via p‐GaN contact layers. A direct Ohmic contact to p‐AlGaN layers should be obtained using UV‐transparent conductive electrodes (TCEs) to solve this problem. A universal method is presented here to make such contact using electrical breakdown, with wide‐bandgap materials, to form conductive filaments (CFs), providing a current path between the TCEs and the p‐(Al)GaN layers. The contact resistance between the TCEs and the p‐GaN layers (or p‐AlGaN) is found to be on the order of 10−5 Ω cm2 (or 10−3 Ω cm2), while optical transmittance is maintained up to 95% for AlN‐based TCEs at 250 nm. These findings could be a critical turning point delivering a breakthrough in UV LED technologies.